Effectiveness of an educational nursing intervention on caring ability and burden in family caregivers of patients with chronic non-communicable diseases. A preventive randomized controlled clinical trial - Myriam Duran Parra; Claudia Consuelo Torres; Ligia Betty Arboleda; Raquel Rivera Carvajal; Sherly Franco; Jenny Santos (Universidad de Antioquia, 2019)
Objective. To evaluate the effect of the "Caring for Caregivers" program in the caring ability and burden in family caregivers of patients with chronic diseases at health care institutions. Methods. A randomized controlled clinical trial was conducted in 34 relatives of patients with chronic diseases that had cared for them for more than 3 months. Zarit scale was used to measure caregiver burden and the CAI (Caring Ability Inventory) was also used to measure caring ability. An educational intervention was applied based on the "Caring for Caregivers" strategy of the Universidad Nacional de Colombia. Results. Although both groups improved their percentage of unburdened caregivers from the first to the second assessment, the difference between the two assessments was 41.2% in the intervention group whereas it was 11.8% in the control group, being only statistically significant the difference for the intervention group. Regarding the caring ability, no significant changes were identified in both groups. Conclusion. On family caregivers, it was observed that the "Caring for Caregivers" intervention had a positive impact on decreasing burden, but not on improving the caring ability.   How to cite this article: Duran M, Torres CC, Arboleda LB, Rivera R, Franco S, Santos J. Effectiveness of an Educational Nursing Intervention on Caring Ability and Burden in Family Caregivers of Patients with Chronic Non-Communicable Diseases. A Preventive Randomized Controlled Clinical Trial. Invest. Educ. Enferm. 2019; 37(1):e04.